Peran Kepemimpinan Kepala Sekolah Dalam Mendukung Budaya dan Mutu SMPK Angelus Custos II Surabaya - Mala, Yuliana Pebristofora marni; Riyanto, Yatim; Widodo, Bambang Sigit (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The role of the headmaster's leadership in supporting the culture and quality of the school is very influential for the quality of the school. This leadership is oriented to how the role of the headmaster's leadership in supporting the interactive learning process, conducive schoolenvironment, cultured and quality community. The purpose of the research is: (1) describe how the role of the headmaster's leadership in supporting the culture of SMPK Angelus Custos II Surabaya (2) describes how the role of the headmaster's leadership in supporting the quality of SMPK Angelus Custos II Surabaya. This research uses Qualitative research method. Data collection using research instruments with participant observation methods, in-depth interviews, documentation and literature reviews. The results of this study are: (1) the role of the principal leadership at SMPK Angelus Custos II Surabaya in supporting the culture and quality of education is considered as an important element and optimal enough in determining the direction of school success. (2) The impact of the principal's support in improving the culture and quality of education at SMPK Angelus Custos II Surabaya is quite maximal. It can be concluded that the role of the headmaster's leadership in supporting the culture and quality of the school is very influential in improving the quality of the school.